Long-term probiotic administration for irritable bowel syndrome: a legal need - Olga I. Solovyeva; Anna S. Nekrasova; Iulia G. Topalova; Viktoriia A. Ponomarenko; Daredzhan B. Tsurtsumiia; Inna G. Ilyashevich (Терапевтический архив, 2023)
Background. Irritable bowel syndrome (IBS) is one of the most common functional diseases of the gastrointestinal tract. Violations in the intestinal microbiocenosis play a significant role in the pathogenesis of this suffering. The probiotic strain Bifidobacterium longum 35624 has a strong evidence base for use in the management of patients with IBS. The duration of probiotic therapy and the need for repeated courses of probiotics require further study, which determined the need for this observational study.